2005
DOI: 10.2116/bunsekikagaku.54.321
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Fluorescence Analysis of Rice and Rice Bran with a Dry Battery X-ray Generator

Abstract: X-ray fluorescence analysis on rice (brown rice, white rice and wash-free rice) and rice bran has been performed by using a dry battery X-ray fluorescence (XRF) spectrometer in combination with a pyroelectric X-ray generator and a potable Si PIN X-ray detector. As a reference, a similar analysis with a commercial energy dispersion XRF spectrometer achieved the detection of K, Mn, Fe, S, Cu, Zn and Rb. The difference of the XRF spectra revealed that K, Fe, Mn, S and Rb were contained in rice bran. Nevertheless,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Radioisotopes, small air-cooled X-ray tubes, or pyroelectric X-ray emitters are used. [11][12][13][14][15][16][17][18][19] Terasawa found that the charge-up of an insulator produced X-rays. 20 He invented an X-ray device, as shown in Fig.…”
mentioning
confidence: 99%
“…Radioisotopes, small air-cooled X-ray tubes, or pyroelectric X-ray emitters are used. [11][12][13][14][15][16][17][18][19] Terasawa found that the charge-up of an insulator produced X-rays. 20 He invented an X-ray device, as shown in Fig.…”
mentioning
confidence: 99%
“…. The sensitivity difference in transition metals, environmental, and rice analyses has been reported after the publication of Ref …”
Section: X‐ray Fluorescence Analysismentioning
confidence: 99%
“…2. The sensitivity difference in transition metals, [10] environmental, [11] and rice analyses [12] has been reported after the publication of Ref. [9] .The authors have also used the pyroelectric X-ray generator for the X-ray absorption spectrometry using an Si-PIN detector [13] and a superconducting energy dispersive X-ray detector.…”
mentioning
confidence: 99%
“…Although several wet chemical analysis methods of fluorine in the slags were proposed, none of them could provide the reliable results. [9,10] Given the importance of AOD slags containing CaF 2 , it became necessary to establish routine instrumental techniques to produce accurate and precise analytical results for process control. Over a number of years, X-ray fluorescence (XRF) spectrometry has been widely employed as a routine instrumental analysis technique for quantifying minerals, slags, oxides, etc.…”
Section: Introductionmentioning
confidence: 99%